2007
DOI: 10.1038/sj.bjc.6603534
|View full text |Cite
|
Sign up to set email alerts
|

Association of FOBT-assessed faecal Hb content with colonic lesions detected in the Florence screening programme

Abstract: We assessed the correlation between quantitative results of immunological faecal occult blood testing (I-FOBT) and colonic lesions (191 colorectal cancers, 890 adenomas) detected at colonoscopy in 2597 FOBT þ (cutoff 100 ng ml À1 Hb) subjects. At univariate analysis, a higher average faecal Hb content was significantly associated with male gender (P ¼ 0.003), age (P ¼ 0.02), and colonoscopy findings (P ¼ 0.000). Among adenomas, higher faecal Hb content was significantly associated with size (P ¼ 0.0000), prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
70
3
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 21 publications
17
70
3
3
Order By: Relevance
“…As in other studies, in our population, the measured intensity of bleeding of invasive cancers was higher than that of high-risk adenomas (Levi et al, 2007;Ciatto et al, 2007). Moreover, we observed lower bleeding intensity in rectal cancers than in cancers in others locations, which is also in line with observations of Ciatto et al (2007) who found smaller although non-significant bleeding amounts for cancers of the rectum þ distal colon rather than proximal colon.…”
Section: Discussionsupporting
confidence: 80%
“…As in other studies, in our population, the measured intensity of bleeding of invasive cancers was higher than that of high-risk adenomas (Levi et al, 2007;Ciatto et al, 2007). Moreover, we observed lower bleeding intensity in rectal cancers than in cancers in others locations, which is also in line with observations of Ciatto et al (2007) who found smaller although non-significant bleeding amounts for cancers of the rectum þ distal colon rather than proximal colon.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, the impact of age, gender, and location of adenomas on performance of the most commonly used screening tests has not been extensively studied. Studies, applying colonoscopy only for FIT-positive individuals, have reported lower positivity rates and stool hemoglobin (Hb) in women, in younger age groups, and subjects with proximal lesions (7,11). As in these studies, colonoscopy data were not available from participants with a negative FIT, it remains unclear whether this discrepancy reflects a lower adenoma rate or possibly a lower sensitivity of FIT in these subgroups.…”
Section: Introductionmentioning
confidence: 41%
“…This negative result may be influenced by several factors contributing to a lower Hb concentration in stool. First, because of an increased degradation of Hb in case of a proximal lesion during colonic passage (11) and second because of the lower mean number and size of adenomas (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Ciatto et al [7] have reported that f-Hb is significantly related to the presence of the very lesions, cancer and advanced adenoma, that screening is aimed at detecting. There is also considerable evidence that f-Hb increases as disease becomes more serious, from the normal to low-risk adenomatous polyps, then to higher-risk polyps and then to cancer, although there is much overlap between these groups [8,9].…”
Section: Introductionmentioning
confidence: 99%